PENGARUH NPL, LDR, ROA, DAN BI RATE TERHADAP PENYALURAN KREDIT BANK PERKREDITAN RAKYAT PROVINSI KALIMANTAN BARAT PERIODE 2012-2014 - B01110087, GUNAWAN (Jurnal Pembangunan dan Pemerataan, 2016)
Rural Bank is one of the banks that give credit to the society. But to give credit bank waseffected by it’s internal factor like LDR, NPL, ROA and eksternal factor like BI Rate. This researchwas aimed to understand how the Non Performing Loan (NPL), Loan to Deposit Ratio (LDR),Return On Assets (ROA), and BI Rate effecting the credit of West Borneo Province Rural Bank on2012-2014 time period. The analysis technique of this research is multiple linear regression. Thesource of the data was from secondary data that published by Indonesian Bank on www.bi.go.id.The results of this research is that the Non Performing Loan, Loan to Deposit Ratio, ReturnOn Assets, and BI Rate simultaneously has a significant effect to the credit, meanwhile partially NonPerforming Loan, Loan to Deposit Ratio, and Return On Asset unsignificantly effecting the credit,but BI Rate positively significant effecting the credit of West Borneo Province Rural Bank on 2012-2014 time period .Keyword : Rural Bank, Non Performing Loan, Loan to Deposit Ratio, Return on Assets, BI Rate,and Credit.